Progress against and nature of the 2013 nutrition for growth comments - Fanzo, Jessica; Manohar, Swetha; Rosettie, Katherine; Glass, Sara (International Food Policy Research Institute, 2016)
ON JUNE 8, 2013, THE GOVERNMENTS OF THE UNITED KINGDOM AND BRAZIL, AND THE CHILDREN’S INVESTMENT FUND FOUNDATION (CIFF) HOSTED A SUMMIT IN London titled “Nutrition for Growth: Beating Hunger through Business and Science” (known as N4G). The objective of the summit was to mark a “seminal declaration by leaders to scale up political commitment, increase resources, and take urgent action on nutrition” (United Kingdom 2013, 1).